On the Physiology of Voice Production in South-Siberian Throat Singing: Analysis of Acoustic and Electrophysiological Evidences - Grawunder, Sven (Frank & Timme, 2009)
Long description: This book presents the first field-work based phonetic study focussing such extraordinary phonatory outcomes as occur in the context of South-Siberian throat singing. In throat singing specific voice production types serve as source, which are subject to various ways of formant shaping, merging, adjustment, and reinforcement, all of which function to enhance individual harmonics. Two main types are proposed for voice production in South-Siberian throat singing: a voice production by means of the vocal folds featuring a constriction of the aryepiglottic sphincter, and a voice production with involvement of the ventricular folds. Furthermore a simple schematic model for the articulation types in throat singing is suggested. One of the basic questions throughout this study is whether the phenomenon of throat singing shows fairly clear regional variants in different parts of southern or whether the variation is chiefly a matter of individual styles. Biographical note: Sven Grawunder studied Speech Science, German Linguistics and Phonetics at the Martin Luther University of Halle-Wittenberg, Germany. He has conducted ethnomusicological, phonetic and linguistic field work in language documentation projects in Siberia, India and Africa. Currently he works as a postdoc researcher at the linguistics department of the Max Planck Institute for Evolutionary Anthropology in Leipzig, Germany.